Employee Productivity of Agribusiness Companies Based on Training and Discipline - Lucky Hikmat Maulana; Rismaya; Sudarijati (Universitas Djuanda, 2020)
Business competition is getting tougher, both locally and globally, requiring companies to increase their productivity with the right strategy. The optimal level of employee productivity will have a positive influence on the company's production and operational activities, both now and in the future. Employee training is one way to increase employee productivity. In addition to training, employee discipline can also increase employee productivity. The purpose of this study is to identify training programs and find out how much influence training and work discipline have on agribusiness company productivity. The object of research is the agribusiness company Packing Section employees. Data were collected through questionnaires, interviews, observations and literature studies. Prior to data analysis, the instrument questionnaire items were processed with validity and reliability tests. Then analyzed with descriptive analysis, linear regression analysis, correlation analysis, coefficient of determination and hypothesis testing. The results showed that the Packing Section employee training was carried out with the apprenticeship method and aimed at improving skills in using small machines to cut vegetables, knowledge of chemical use and firefighting training, and instructors from internal company. Research concludes that training has a significant effect on employee productivity, while work discipline has no significant effect on employee productivity. However, simultaneous training and work discipline have a significant effect on employee productivity